Representasi Matematis Siswa Bergaya Kognitif Visualizer-Verbalizer dalam Menyelesaikan Soal Matematika TIMSS - M. Syahid; Kurnia Noviartati (Jurnal Gantang, 2019)
This study aims to describe students' mathematical representations in a cognitive style of visualizers in solving TIMSS problems. This research is a qualitative descriptive study. In this study consisted of 4 students where 2 of them were students with low and high cognitive style visualizers, and 2 others were students with low and high cognitive verbalizer styles. The instruments in this study were the researchers themselves and assisted with cognitive style questionnaire sheets, TIMSS test sheets, and interview guidelines. Data collection techniques used were in the form of cognitive style tests, TIMSS test questions, and student interviews. The technical data analysis used is data reduction, data presentation, and drawing conclusions. The results of this study are that mathematical representations with cognitive visualizer style are able to work on the questions in the form of images or illustrations well through the stages set by the researcher, namely; the interest in the question according to its cognitive style, understanding the problem more than the student who has a positive verbalizer style, uses a better solution to approach the perfection of the answer. Students' mathematical representations in the cognitive verbalizer style are able to work on questions presented with story or narrative questions that are easier to understand and able to describe well and are able to represent in mathematical languages.